Sustainable Choices in Bottled Water: Linking Green Product and Brand Image to Repurchase Intention Through Trust and Satisfaction – A Study of Consumers in Jakarta - Maria Novendra Tyas Ayu; Sudharto P Hadi (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study examines the influence of green product attributes and green brand image on consumers’ green repurchase intention, with green trust and green satisfaction serving as mediating variables, in the context of Danone Aqua Life consumers in Jakarta. Employing a quantitative research design, data were gathered through a structured questionnaire administered to 145 respondents. The study reveals that green product attributes and green brand image positively influence green trust and green satisfaction, both of which significantly boost green repurchase intention. Mediation analysis shows that green trust and green satisfaction partially mediate the links between the independent variables (green product, green brand image) and the dependent variable (green repurchase intention). Grounded in the Theory of Planned Behavior, the findings highlight how trust and satisfaction shape consumers’ intentions to repurchase eco-friendly products, offering practical implications for enhancing sustainable marketing strategies in the bottled water industry.